The vascular collar of the ilium— Three‐dimensional evaluation of the dominant nutrient foramen. Issue 4 (18th January 2013) - Cunningham, Craig A.; Black, Sue M.
Abstract: Nutrient arteries are the predominant blood supply to endochondral bones and are particularly important during the early stages of endochondral ossification and the active growth period. These nutrient vessels traverse the periosteal shell of a developing bone to invade the disintegrating cartilage matrix and bring about endochondral bone formation. This results in the formation of a nutrient foramen which is retained as the vascular conduit between the exterior and interior of the bone. This study examined the dominant nutrient foramen of the neonatal ilium using high resolution micro‐computed (micro‐CT) tomography. Three‐dimensional reconstruction of micro‐CT data consistently demonstrated the presence of a distinctive, yet poorly reported, collar of bone extending into the trabecular cavity beyond the endosteum. This study proposes that this collar of bone may have formed in response to osteogenic signaling from approximated arterial vasculature. Additionally, it is suggested that the formation of this collar may act as a protective mechanism to the dominant nutrient vessel and as a potential biomechanical anchor for surrounding trabeculae, aiding to increase the biomechanical competency around the area of the foramen. The documentation of this osteological structure is important from a clinical perspective to prevent the misinterpretation of fracturing and pathology on plain plate radiographs and clinical computed tomography scans. Clin. Anat., 2013. © 2013 Wiley Periodicals, Inc.